Making the Moral Case for Social Sciences: Stemming the Tide - Spracklen, Karl.; SpringerLink (Online service) (London : Palgrave Macmillan UK(Imprint), 2016)
The social sciences have a legitimacy problem in the modern world. The natural sciences are viewed as 'proper science' by journalists and policy-makers because they discover 'truths', make money, and help governments solve problems. In turn, defenders of the social sciences borrow the language of instrumentality, profit and policy impact. Karl Spracklen, by contrast, makes the moral case for the social sciences, arguing that they are a necessary social good capable of fighting inequality and revealing the workings of hegemonic power.
Keywords: Social sciences-Philosophy.; Social sciences -- Methodology; Social Structure, Social Inequality